Metabolomic profiling of rhodosporidium toruloides grown on glycerol for carotenoid production during different growth phases - Lee, Jaslyn Jie Lin (2015)
Carotenoid production from three strains of Rhodosporidium toruloides grown on glycerol was studied. A time-dependent metabolomics approach was used to understand its metabolism on glycerol and mechanism for carotenoid production in three strains during different growth phases (1, 4, 7, and 12 days). Strain CBS 5490 was the highest carotenoid producer (28.5 mg/L) and had a unique metabolic profile. In this strain, metabolites belonging to the TCA cycle and amino acids were produced in lower amounts, as compared to the other strains. On the other hand, it produced the highest amounts of carotenoid and fatty acid metabolites. This indicated that the lower production of the TCA cycle and amino acid metabolites promoted energy and metabolic flux toward the carotenoid and fatty acid synthesis metabolic pathways. This study shows that metabolomic profiling is a useful tool to gain insight into the metabolic pathways in the cell and to shed light on the different molecular mechanisms between strains.